A FEW OBSERVATIONS ON THE BIOLOGY OF TACHYSURUS THALASSINUS RUPPELL FROM VERAVAL (GUJARAT) - RAJE, SADASHIV GOPAL (Journal of Indian Fisheries Association, 2015)
The length-weight relationship o.t; Ethalassinus differed in the sexes and, thereforeseparate equations were obtained; for males log W = -5.1728 4- 3.0495 log L; and for femaleslog W = -5.7456 + 3.2798 log L. The spawning period of this species appears to be restricted toa short period from October to November. Fecundity has been found to range from 33 to 55mature eggs in specimens of the size range 421-564nun, The sex ratio of males to females was1.8:1. T.thalassintis is a bottom carnivore, crustaceans ranking first in food followed by fishes,molluscs and polychaetes.